The economic activities analysis of the marginal community living around the artisanal oil mining site in Hargomulyo, Bojonegoro Regency - N T Brata; S Sairin; S Setiadi (Journal of Degraded and Mining Lands Management, 2017)
The focus of this paper is on a marginal society in Bojonegoro Regency, East Java Province. It is a remote area in the middle of a teak forest, far away from the centre of economy and governance, it’s that makes the society find some difficulties to overcome their economic problems. There are some oil wells owned by NV BPM Company which had stopped its legal operations. Then, the society conducts illegal traditional oil mining. The purposes of this study are: (1) to study the reason of the society in making the artisanal oil mining as their livelihood, (2) to study the economic implication from their mining activities. The results showed that in a tough life to fulfil their needs, there is a creative idea from the society in seeing and understanding their infertile environment. In an environment that looks unable to provide a chance to the society for getting a livelihood, there are some people find a niche in the form of old oil wells. The society is able to find an environment niche to resolve their poverty problems. The economic implication is in the form of chance or entrance for the society to work in Artisanal Oil Mining (AOM) field.